Transduction matrix to enable sensor-less application of DC motor - Ivan Tanra; Shih-fu Ling (Diponegoro University Semarang Indonesia, 2019)
Sensorless technology is one of the popular topic in motor industry. The aim is to reduce number of sensor and sensor size in the system. One of the method to achieve this sensor-less application of a motor is thru transduction matrix method. Transduction matrix is a 2x2 matrix that show the relationship between electrical input and mechanical output of the motor. By obtaining the transduction matrix of a chosen motor, the mechanical output of the motor can be calculated from its electrical input. This paper explains the theory behind and the method to obtain the transduction matrix of a DC motor. The DC motor is chosen because it is the common motor in industry.